INOVASI APLIKASI ASESMEN NASIONAL MENGGUNAKAN TEKNOLOGI PROGRESSIVE WEB APP - Muhamad Aslan, La Ode; Yusri, Iin Karmila; Raharjo , Muh. Fajri (Politeknik Negeri Ujung Pandang, 2024)
The national assessment is a program for assessing the quality of each school, madrasah and equality program at the primary and secondary levels. The national assessment application utilizes network connectivity to send national assessment results data from the application to the server. However, the lack of equal distribution of network facilities and infrastructure is an obstacle in the use of national assessment applications. Therefore, to build a national assessment application system that can be accessed without having to depend on network connectivity, the system will be built using the Progressive Web App (PWA) concept. Meanwhile, by using the web app manifest, the website can bring up a pop-up add to homescreen which is useful for installing the system on the user's homescreen so that applications can be accessed quickly via the homescreen icon. By using indexedDB, even though in an offline state the user can still send data and the data will be saved to indexedDB and when the network returns online the data will be automatically synchronized with the server. From the results of testing the quality of PWA using Lighthouse, there is a decrease in the performance of the progressive web app application each time the number of users is added, this indicates that the number of users can affect the performance of a computer-based national assessment application using a progressive web app.